The role of lipids in cancer progression and metastasis - Martin-Perez, Miguel; Urdiroz-Urricelqui, Uxue; Bigas, Claudia; Benitah, Salvador Aznar (Cell metabolism, 2022)
Lipids have essential biological functions in the body (e.g., providing energy storage, acting as a signaling molecule, and being a structural component of membranes); however, an excess of lipids can promote tumorigenesis, colonization, and metastatic capacity of tumor cells. To metastasize, a tumor cell goes through different stages that require lipid-related metabolic and structural adaptations. These adaptations include altering the lipid membrane composition for invading other niches and overcoming cell death mechanisms and promoting lipid catabolism and anabolism for energy and oxidative stress protective purposes. Cancer cells also harness lipid metabolism to modulate the activity of stromal and immune cells to their advantage and to resist therapy and promote relapse. All this is especially worrying given the high fat intake in Western diets. Thus, metabolic interventions aiming to reduce lipid availability to cancer cells or to exacerbate their metabolic vulnerabilities provide promising therapeutic opportunities to prevent cancer progression and treat metastasis. [Display omitted] In this review, Martin-Perez et al. discuss recent discoveries involving the effect of lipids during cancer progression. Lipids are required for energy and membrane adaptations during the metastatic cascade but also impact cellular signaling and the tumor microenvironment, which offers distinct metabolic vulnerabilities to treat metastasis. Importantly, these lipid-mediated mechanisms seem to be potentiated when diets are enriched in fat.